KESEHATAN PEKERJA INFORMAL DITINJAU DARI PENDIDIKAN, UPAH DAN KETERSEDIAAN LAPANGAN PEKERJAAN - Kurniawan, Heru; Abdullah, Imam; Pranitamotik, Dewi (Komunitas Manajemen Kompetitif, 2025)
Informal workers are of particular concern because they face the greatest health risks, so research needs to be conducted to see whether education, wages and employment opportunities can address the health dynamics of informal workers. This study uses multiple regression with panel data to determine the distribution of the impact of independent variables. The results of this study indicate that when education and wages increase, the health quality of informal workers also improves, and vice versa. However, employment opportunities do not have a significant impact because health is a prerequisite for obtaining job opportunities. Provinces with an average decline in health are those with low education levels and high mobility. The government needs to improve education and raise wage standards in provinces with high health risks, as well as implement policies related to the provision of healthcare facilities at the workplace.